The CAMHS referral process : the perspectives of school counsellors on the front line of youth mental health in Aotearoa New Zealand : a thesis presented in partial fulfilment of the requirements for the degree of Master of Science in Psychology at Massey University, Manawatū, Aotearoa New Zealand - Holland, Ashley (Massey University, 2025)
School counsellors are fundamental to supporting the mental health of young people in Aotearoa New Zealand. They are crucial in not only providing primary care services but also for facilitating the referral to Child and Adolescent Mental Health Services (CAMHS) when counselling alone is not sufficient. Mental health in Aotearoa New Zealand is increasing in both prevalence and severity, rangatahi mirroring this nationwide trend. There are significant stressors influencing all key stakeholders involved with supporting rangatahi mental health, with strains on public mental health services such as CAMHS. There is a disparity between CAMHS nationwide, in both service and delivery processes. As school counsellors are responsible for many of the referrals made to CAMHS, this research study gathered perspectives from school counsellors to shed light on the current state of the referral process. Method: Participants completed a mixed methods designed online survey, and the responses were analysed using both descriptive statistical analysis and reflexive thematic analysis. Results: School Counsellors identified key areas of strengths, weaknesses and changes needed within the CAMHS service. A list of beneficial next steps for CAMHS was generated. Conclusion: There is a considerable need for a more responsive CAMHS referral process in Aotearoa New Zealand, catering for the increasing complexity and demand of rangatahi mental health. There are both strengths and weaknesses of the current CAMHS referral process, and with collaboration and cooperation with school counsellors they will be able to implement changes which will improve this process, benefiting vulnerable rangatahi.
Keywords: 520303 Counselling psychology; 420313 Mental health services